Primary Hyperparathyroidism overlapping with Multiple Sclerosis: a catastrophic marriage: - Cervellin, Gianfranco; Brianti, Vincenzo; Viani, Lorenzo; Feldmann, Lucia; Rastelli, Gianni (Acta Biomedica Atenei Parmensis, 2023)
Primary hyperparathyroidism (PHPT) often leads to neurological or psychiatric disorders, thus mimicking different diseases. Here we present a 77-years old man visited in the Emergency Department complaining for fatigue, multiple falls, nausea, anorexia, and constipation. Symptoms were rapidly worsening, and on admission he appeared sleepy, responsive to verbal stimulus, disoriented, dehydrated, unable to maintain upright position. He suffered from mild, relapsing and remitting Multiple Sclerosis (MS) since the age of 45, at that moment not requiring treatment. The laboratory tests displayed severe hypercalcemia (16.8 mg/dL), slightly decreased level of serum phosphorus (2.8 mg/dL), very high levels of parathyroid hormone (PTH) (508 pg/mL). A parathyroid mass (35x21x32 mm) in left paratracheal position was found with Computed Tomography (CT) of the neck. After correcting hypercalcemia, he was operated on day 18, thus confirming the parathyroid adenoma, that was successfully removed. One month later, the patient was completely well, and able to walk without any help, like three months before. The lab tests’ values obtained during the control visit showed complete normalization of calcium-phosphate metabolism. Diabetes, too, was going better, allowing a reduction in metformin dosage. At the best of our knowledge this is the first described case of a clinically significant overlapping between symptoms due to a long-lasting mild MS and an unrecognized, severe, PHPT. This case underlines the importance of a thorough metabolic evaluation of each patient presenting worsening of his neuromuscular and/or neuropsychiatric condition, even when previously known to be affected by a defined neurologic or psychiatric disease.